2020
DOI: 10.1186/s13195-020-00604-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in cognitively normal older persons, and the association with Alzheimer’s and non-Alzheimer’s dementia

Abstract: Background: Neuropsychiatric symptoms (NPS) have been reported to be useful in predicting incident dementia among cognitively normal older persons. However, the literature has not been conclusive on the differential utilities of the various NPS in predicting the subtypes of dementia. This study compared the risks of Alzheimer's and non-Alzheimer's dementia associated with the various NPS, among cognitively normal older persons. Methods: This cohort study included 12,452 participants from the Alzheimer's Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 63 publications
1
65
2
4
Order By: Relevance
“…The Cox regression adjusted for demographic information (age, sex, and ethnicity), known predictors of neurocognitive disorders (years of education, APOE e4 status, current smoking, diabetes mellitus, hypertension, hyperlipidemia, and MMSE score) [ 29 ], as well as potential confounders [ 30 ] that may predict both the exposure-of-interest (SCD) and the outcome-of-interest (neurocognitive disorders), namely GDS score and presence of anxiety symptoms. GDS score was included as a potential confounder because depressive symptoms are strongly associated with SCD (exposure-of-interest) [ 1 , 8 , 31 , 32 ], while at the same time, the presence of depressive symptoms has been shown to be an independent predictor of neurocognitive disorders (outcome-of-interest) [ 3 , 33 35 ]. Similarly, anxiety symptoms are known to correlate with SCD (exposure-of-interest) [ 2 ], and the presence of anxiety symptoms has also been reported to predict neurocognitive disorders (outcome-of-interest) [ 33 – 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cox regression adjusted for demographic information (age, sex, and ethnicity), known predictors of neurocognitive disorders (years of education, APOE e4 status, current smoking, diabetes mellitus, hypertension, hyperlipidemia, and MMSE score) [ 29 ], as well as potential confounders [ 30 ] that may predict both the exposure-of-interest (SCD) and the outcome-of-interest (neurocognitive disorders), namely GDS score and presence of anxiety symptoms. GDS score was included as a potential confounder because depressive symptoms are strongly associated with SCD (exposure-of-interest) [ 1 , 8 , 31 , 32 ], while at the same time, the presence of depressive symptoms has been shown to be an independent predictor of neurocognitive disorders (outcome-of-interest) [ 3 , 33 35 ]. Similarly, anxiety symptoms are known to correlate with SCD (exposure-of-interest) [ 2 ], and the presence of anxiety symptoms has also been reported to predict neurocognitive disorders (outcome-of-interest) [ 33 – 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…GDS score was included as a potential confounder because depressive symptoms are strongly associated with SCD (exposure-of-interest) [ 1 , 8 , 31 , 32 ], while at the same time, the presence of depressive symptoms has been shown to be an independent predictor of neurocognitive disorders (outcome-of-interest) [ 3 , 33 35 ]. Similarly, anxiety symptoms are known to correlate with SCD (exposure-of-interest) [ 2 ], and the presence of anxiety symptoms has also been reported to predict neurocognitive disorders (outcome-of-interest) [ 33 – 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from a Mexican cohort study showed that certain NPS were independent predictors of incident dementia after 3 years [15] and data from the Mayo Clinic Study of Aging indicated that agitation, apathy, anxiety, irritability, and depression in cognitively normal persons predicted incident MCI [10]. Results from a recent longitudinal study on cognitively normal persons showed that psychotic, affective, and agitation symptoms predicted Alzheimer's dementia, among other dementia subtypes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common NPS in patients with mild cognitive impairment (MCI) and early AD are depression, agitation, and apathy [2], but also anxiety and irritability that show a high prevalence especially in MCI [3,4]. In cognitively normal persons of the National Alzheimer's Coordinating Center (NACC) database who progressed to dementia over the median follow-up of 4.7 years, the most prevalent NPS were depression, irritability, sleep disturbances, appetite changes, and anxiety [5].…”
Section: Introductionmentioning
confidence: 99%